Chitosan/Solid-Lipid Nanoparticles Hybrid Gels for Vaginal Delivery of Estradiol for Management of Vaginal Menopausal Symptoms - Heba A. Abou-Taleb; Zeinab Fathalla; Demiana M. Naguib; Adel Al Fatease; Hamdy Abdelkader (Pharmaceuticals, 2023)
Hormonal replacement therapy is the mainstay treatment to improve quality of life and reduce mortality. With the increasing number of young women with early menopause, women now live longer (increased life expectancy). However, poor patient compliance with oral estrogen therapy has emerged. Intravaginal estrogen therapy can provide significant benefits with minimal risk for postmenopausal women with symptoms of the lower urinary tract and vaginal area but who do not want to take oral estrogen. In this study, estradiol-loaded solid lipid nanoparticles (SLPs) were prepared from compritol ATO 888 and precirol ATO 5, and two different stabilizers (Pluronic F127 and Tween 80) were studied. Selected SLPs (F3 and F6) were coated with different concentrations of the mucoadhesive and sustained-release polymer chitosan. Furthermore, gelation time, viscosity, mucoadhesion, ex vivo permeation, and in vitro irritation for vaginal irritation were studied. Particle sizes ranged between 450–850 nm, and EE% recorded 50–83% for the six SLPs depending on the type and amount of lipids used. Cumulative % drug release was significantly enhanced and was recorded at 51% to 83%, compared to that (less than 20%) for the control suspension of estradiol. Furthermore, extensive thermal gelation and mucoadhesion were recorded for chitosan-coated SLPs. Up to 2.2-fold increases in the permeation parameters for SLPs gels compared to the control suspension gel were recorded, revealing a slight to moderate irritation on Hela cell lines. These findings demonstrated chitosan-coated estradiol SLPs as novel and promising vaginal mucoadhesive hybrid nanogels.